The Impact of Service and Savings Product Quality on Customer Satisfaction at Bank Central Asia (BCA) Malang City - Naiandra Permana, Keikoo Revashthie Dzikra; Dewi, Mariana Puspa (Manajemen Multitalenta Indonesia, 2025)
Banks are financial institutions that guarantee the smooth circulation of money within society. As financial management entities, banks offer various services, such as credit, savings, and loans. In Indonesia, banking operations are protected by a legal framework. This research employs a quantitative methos with a causal relationship approach, analyzing the influence of Service Quality (X1) and Savings Product Quality (X2) on Customer Satisfaction (Y). Sampling was conducted through probability sampling using simple random sampling technique, involving 54 respondents. Data collection utilized questionnaires that underwent validity and reliability testing. Data analysis employed multiple linear regression to test the research hypothesis. The research findings indicate that: (1) service quality has a positive and significant impact on customer satisfaction, (2) savings product quality also positively and significantly influences customer satisfaction, (3) service quality and savings product quality simultaneously have a positive and significant effect on customer satisfaction levels.